The DESCRIPTION OF KNOWLEDGE, ATTITUDE, AND ACTIONS OF THE YOUTH OF KARANG TARUNA MARDISARI IN WASTE MANAGEMENT - Lestari, Ratna; Ferianto, Ferianto; Ikmal, Muhammad; Yusriana, Yusriana (Program Studi Keperawatan Universitas Jambi, 2025)
Environmental pollution due to household waste remains a common problem in society that has not received serious attention. This is caused by the lack of public awareness about a healthy environment. Awareness will emerge through knowledge and a good attitude as well as real action to process waste correctly. This awareness is the responsibility of everyone, including youth organizations. As a platform for the younger generation, youth organizations can actively participate in creating cleanliness in the community through waste processing.. This study aims to describe youth knowledge, attitudes, and practices in managing waste in Mardisari, Kertosari, Temanggung. This study used a quantitative descriptive research design with 55 Mardisari youth as sample from a total population of 125 people by used simple random sampling technique. Data is collected by using questionnaires of knowledge, attitude, and practice about waste management. Data is analyzed by univariate analysis. This study shows that most of the youth are include in early adulthood (58.2%), female gender (58.2%), high school education (69.1%). Meanwhile, the description of youth knowledge was in the poor category (56.4%), their attitudes was negative (61.8%), their practices was in the poor category (58.2%). This result is expected to serve as a reference for the youth and the officials of Mardisari Village to play an active role in environmental protection by managing waste to create a healthy environment.